The Mechanisms and Therapeutic Implications of PI3K Signaling in Airway Inflammation and Remodeling in Asthma - Song B; Hu J; Chen S; Zhang Y (Biologics: Targets & Therapy)
Bangguo Song,1 Jihong Hu,2,3 Shupeng Chen,4 Yang Zhang5,6 1School of Clinical Chinese Medicine, Gansu University of Traditional Chinese Medicine, Gansu, People’s Republic of China; 2Teaching Experimental Training Center, Gansu University of Traditional Chinese Medicine, Gansu, People’s Republic of China; 3Key Laboratory of Traditional Chinese Herbs and Prescription Innovation and Transformation of Gansu Province, Lanzhou, People’s Republic of China; 4School of Clinical Medicine, Jiangxi University of Traditional Chinese Medicine, Jiangxi, People’s Republic of China; 5Key Laboratory of Dunhuang Medicine and Transformation, Ministry of Education, Gansu, People’s Republic of China; 6Scientific Research and Experimental Center, Gansu University of Chinese Medicine, Lanzhou, People’s Republic of ChinaCorrespondence: Jihong Hu, Teaching Experimental Training Center, Gansu University of Traditional Chinese Medicine, Gansu, People’s Republic of China, Email hujihonghappy@163.comAbstract: Bronchial asthma is a complex and heterogeneous disease with ongoing airway inflammation and increased airway responsiveness. Key characteristics of the disease include persistent airway inflammation, airway hyperresponsiveness, and airway remodeling. Asthma’s chronic and recurrent characteristics contribute to airway remodeling and inflammation, which can exacerbate lung damage. Presently, inflammation is predominantly managed with corticosteroids, yet there is a notable absence of treatments specifically addressing airway remodeling. The phosphoinositide 3-kinase (PI3K) signaling pathway is integral to the processes of inflammation, airway remodeling, and immune responses. Pharmacological agents targeting this pathway are currently undergoing clinical evaluation. This review elucidates the role of PI3K in the immune responses, airway inflammation, and remodeling associated with asthma, examining its underlying mechanisms. Furthermore, we synthesize the existing literature on the therapeutic potential of PI3K inhibitors for asthma management, emphasizing immune modulation, airway inflammation, and remodeling, including drug development and ongoing clinical trials. Lastly, we explore how various PI3K-targeted therapies may enhance efficacy and improve tolerance. Keywords: asthma, PI3K, inflammation, airway remodeling, inhibitor, immune responses